Valuation of goods and services produced by coppice and high forest management alternatives in the Pabuçdere Watershed - (:unkn) unknown (My University, 2020)
To effectively manage forest resources, consideration of all benefits provided by forests in management decisions is necessarily required. In this study, the value of benefits gained through management approaches such as coppice forest and high forest was estimated using choice experiments. According to this method, 16 different choice sets were created to include the combination of the level of benefits. There are three forest management options-one status quo (current situation) and two different management options in each choice set. This study aimed to determine the effect of possible management options on marketable and nonmarketable benefits produced by different types of forest management regimes in the Pabuçdere watershed. Four ecosystem benefits in form of resources such as timber, water, wildlife, and mushroom were considered. A face-to-face survey was conducted on 384 respondents living in villages inside and near the watershed. Data obtained were analyzed using conditional logit and random parameter logit models with the NLOGIT 5.0 statistical program. Marginal values of the benefits for different parts of the research area and the annual total economic value of each option were calculated. Results revealed that changes in forest management approaches cause a corresponding change in the values added by the society. Considering social preferences as a whole, the more number of “high forests” in the Pabuçdere watershed, the more is the value added by the society to forest services.

Etkin orman kaynakları yönetim kararları alabilmek için, olası orman yönetim seçeneklerinin üretebildiği tüm faydaları dikkate almak gerekmektedir. Bu çalışmada, baltalık ve koru ormanı şeklindeki iki ayrı orman yönetim seçeneğiyle elde edilen faydaların değerleri, Seçim Deneyleri Yöntemi kullanılarak hesaplanmıştır. Yöntem gereği, fayda seviyelerinin kombinasyonunu içeren, 16 farklı seçim seti oluşturulmuştur. Her bir seçim setinde, bir mevcut durum ve iki farklı yönetim seçeneği içeren, toplamda üç orman yönetimi alternatifi yer almıştır. Çalışmanın amacı, Pabuçdere Havzasında orman yönetim seçenekleri tarafından üretilen, pazarı olan ve olmayan faydalar üzerinde olası yönetim seçeneklerinin etkisini belirlemektir. Bu amaçla çalışmada, odun hammaddesi, su, yaban hayatı ve mantar gibi dört ekosistem faydası ele alınmıştır. Çalışma verileri havza içerisinde ve yakınındaki köylerde yaşayan 384 kişi ile yüz yüze yapılan anketlerden elde edilmiştir. Veriler, NLOGIT 5.0 istatistik programıyla, Koşullu Logit ve Tesadüfi Parametre Logit modelleri kullanılarak analiz edilmiştir. Analizler sonucunda araştırma alanının farklı bölümleri için sağlanan faydaların marjinal değerleri ve her bir yönetim seçeneğinin yıllık toplam ekonomik değeri hesaplanmıştır. Sonuçlar, orman yönetim şekilleri değiştiğinde toplumun atfettiği değerlerin de değiştiğini ortaya koymaktadır. Buna göre, toplumsal tercihler bir bütün olarak ele alındığında, Pabuçdere havzasında koru ormanı arttıkça toplumun orman hizmetlerine verdiği değerin de arttığı görülmüştür.
Pabuçdere Havzasında baltalık ve koru orman yönetim seçeneklerinin ürettiği mal ve hizmetlerin değerinin belirlenmesi